2009
DOI: 10.1890/07-2092.1
|View full text |Cite
|
Sign up to set email alerts
|

Golf courses and wetland fauna

Abstract: Abstract. Golf courses are often considered to be chemical-intensive ecosystems with negative impacts on fauna. Here we provide evidence that golf courses can contribute to the support and conservation of wetland fauna, i.e., amphibians and macroinvertebrates. Comparisons of amphibian occurrence, diversity of macroinvetebrates, and occurrence of species of conservation concern were made between permanent freshwater ponds surveyed on golf courses around Sweden's capital city, Stockholm, and off-course ponds in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 69 publications
1
18
0
1
Order By: Relevance
“…areas where >75% of the area (looking at each 1 × 1 km square) is developed, as defined by the Swedish mapping, cadastral and land registration authority (Lantmäteriet). This meant that, for example, ponds located in golf courses were excluded, even though they usually have high potential value for biodiversity in urban areas (Colding et al 2009). …”
Section: Study Area and Pond Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…areas where >75% of the area (looking at each 1 × 1 km square) is developed, as defined by the Swedish mapping, cadastral and land registration authority (Lantmäteriet). This meant that, for example, ponds located in golf courses were excluded, even though they usually have high potential value for biodiversity in urban areas (Colding et al 2009). …”
Section: Study Area and Pond Selectionmentioning
confidence: 99%
“…They also provide important habitats for species that would otherwise not survive in the urban environment (Colding et al 2009;Hill and Wood 2014;O'Brien 2015). While ponds in rural landscapes have been well investigated (Biggs et al 2005;Céréghino et al 2008;Davies et al 2008), there are far fewer studies about the biodiversity of these environments located in cities.…”
Section: Introductionmentioning
confidence: 99%
“…1. Of course, this assumption has its exceptions-an interesting local case being the ponds maintained by golf course managers (Colding et al 2009). Although some wetlands are privately owned, only the municipalities develop comprehensive spatial plans of larger areas.…”
Section: Study Sitementioning
confidence: 99%
“…The capacity of flood storage in manmade lakes of golf course is of great significance for surrounding urban areas (Bolund and Hunhammar, 1999). Colding et al (2009) found that man-made lakes in golf course have a more homogenous species composition than ponds in nature-protected areas and ponds in residential parkland. This study also suggested that golf courses may significantly contribute to wetland fauna support, particularly in urban settings.…”
Section: Introductionmentioning
confidence: 99%